2011
DOI: 10.1007/s11426-010-4179-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiviral bioactivities of novel chiral bis-thiourea-type derivatives containing α-aminophosphonate moiety

Abstract: Starting from 1-((1R,2R)-2-aminocyclohexyl)-3-substituted thioureas (3a-c) and substituted isothiocyanates (9a-d), chiral bis-thiourea derivatives containing -aminophosphonate moiety 10a-l were prepared and completely characterized by elemental analysis, physical and spectral (IR, 1 H NMR, 13 C NMR, 31 P NMR) data. The results of bioassay revealed that compounds 10a and 10e possessed appreciable curative bioactivities on cucumber mosaic virus (CMV) at 0.5 mg/mL in vivo (inhibitory rate = 60.3%, 64.8% respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Li et al also used the chiral molecules derived from NPs (Zhang, Li, et al, ,2017Zhang, Wang, et al, 2018). Since 2009, Song and co-workers have been attempting to develop chiral antiviral agent by constructing a series of chiral phosphonate moieties using inexpensive, commercially available chiral amine (Chen et al, 2009), (R,R)-1,2diaminocyclohexane (Yang et al, 2011) and L-Boc-leucine (Liu et al, 2010) as the chiral building blocks. Recently, Li and co-workers synthesized two chiral succinate dehydrogenase inhibitors (SDHIs), (R)-2-chloro-N-(2-(4-ethyl-4,5dihydrooxazol-2-yl) phenyl)nicotinamide (SDHIs-1) and N-(2-((R)-4-ethyl-4,5-dihydrooxazol-2-yl) phenyl)-2-hydroxy-2-phenylacetamide (SDHIs-2) using chiral building blocks.…”
Section: Chiral Compounds Have High Potential As Agrochemicalsmentioning
confidence: 99%
“…Li et al also used the chiral molecules derived from NPs (Zhang, Li, et al, ,2017Zhang, Wang, et al, 2018). Since 2009, Song and co-workers have been attempting to develop chiral antiviral agent by constructing a series of chiral phosphonate moieties using inexpensive, commercially available chiral amine (Chen et al, 2009), (R,R)-1,2diaminocyclohexane (Yang et al, 2011) and L-Boc-leucine (Liu et al, 2010) as the chiral building blocks. Recently, Li and co-workers synthesized two chiral succinate dehydrogenase inhibitors (SDHIs), (R)-2-chloro-N-(2-(4-ethyl-4,5dihydrooxazol-2-yl) phenyl)nicotinamide (SDHIs-1) and N-(2-((R)-4-ethyl-4,5-dihydrooxazol-2-yl) phenyl)-2-hydroxy-2-phenylacetamide (SDHIs-2) using chiral building blocks.…”
Section: Chiral Compounds Have High Potential As Agrochemicalsmentioning
confidence: 99%
“…Likewise the aminophosphonic acids, they are able to inhibit enzymes involved in amino acids metabolism, and thus may generate various physiological responses, e.g., neuromodulatory activity [358]. Cucumber mosaic virus (CMV) and tobacco mosaic virus (TMV) are plant virus diseases which have become a serious problem in agriculture in recent years [359]. The commercially available product Ningnanmycin is commonly used against CMV and TMV, though with serious limitations resulting from its light and moisture sensitivity.…”
Section: Antiviral Thioureasmentioning
confidence: 99%
“…It was also found that the absolute configuration of isothiocyanates, used to form corresponding mono-and bis-thioureas, considerably affected the antiviral activity of tested compounds. Generally, mono-thiourea (S)-enantiomers were more effective against TMV than corresponding (R)-enantiomers [320], while the results for bis-thioureas against CMV appeared to be reversed: derivatives obtained from (R)-enantiomer of isothiocyanate were more active against the virus [359]. Molecules 2020, 25 Liu and co-workers prepared a series of chiral thioureas bearing t-leucine and αaminophosphonate moieties and evaluated their anti-TMV activity [360].…”
Section: Antiviral Thioureasmentioning
confidence: 99%
See 2 more Smart Citations